Loopholes in the Research Ethics System? Informed Consent Waivers in Cluster Randomized Trials with Individual‐Level Intervention. Issue 6 (2nd November 2020) - London, Alex John; Taljaard, Monica; Weijer, Charles
ABSTRACT: Individual‐cluster trials randomize groups of individuals but deliver study interventions directly to individual participants. We examine three arguments that might justify the perception that the bar for a waiver of consent should be lower in such trials than for individually randomized trials. We contend that if these arguments are treated as sufficient to grant a waiver of consent, then a loophole emerges in research oversight. Such loopholes are morally hazardous for study participants, the integrity of science, and public trust in the research enterprise. We conclude by articulating the standards that research ethics committees should use to evaluate requests for waivers of consent in individual‐cluster trials.